The Querelle des Femmes in Sixteenth-Seventeenth-Century Philosophy: Ideas of Platonism and Aristotelianism in the Grand Duchy of Lithuania and Europe - Čitavičiūtė, Dovilė (Senoji Lietuvos literatūra, 2025)
The article examines the reception of Plato and Aristotle’s philosophy in shaping attitudes towards women in the Grand Duchy of Lithuania and Europe in the sixteenth–seventeenth centuries. It examines how various philosophical treatises, dialogues, and Aristotle’s commentaries influenced intellectual discourse beyond their cultural origins, thus creating a basis for a philosophical understanding of the role of women in the family and society of the Grand Duchy of Lithuania. The article juxtaposes the views of Platonists and Aristotelians on women. Platonism, especially in Renaissance court culture, offered a more progressive perspective. Through such works as Baldassare Castiglione’s Il cortegiano (1528) and Łukasz Górnicki’s Dworzanin polski (1566; The Polish Courtier), the article highlights the differences between Western European and Polish-Lithuanian court societies. Although constrained by certain patriarchal norms, Castiglione’s lady-in-waiting actively participated in public life by engaging in refined conversation, musical activities, and dance. Górnicki’s adaptation, which was shaped by conservative Polish and Lithuanian culture, basically confined women to private domestic roles, but still required them to be as refined as male courtiers. Unlike the Italian courts, where ladies-in-waiting were integrated into cultural and intellectual life, Polish and Lithuanian aristocracy saw women primarily as wives and mothers responsible for managing the household and moral virtue. On the other hand, during the Renaissance and Baroque periods Aristotle’s philosophy was invoked to confirm and substantiate the attitudes towards women prevailing at the time and was therefore popular throughout Europe, especially in more conservative cultural spaces such as universities and colleges. Such thinkers as Bartholomäus Keckermann (c. 1572–1609) and Aaron Alexander Olizarowski (Olizarovius, 1610–1659) argued for male dominance, justifying it by natural hierarchy and theological reasoning. A man’s duty is to legally protect his wife, advise her, and look after her, but he does not have unlimited authority (potestas) over her. Extrapolating from Aristotle’s Politics (1260a 11), commentators argued that women had to be more or less subordinate to men because they were less intelligent and lacked willpower by nature. Various passages in Nicomachean Ethics that discuss imperfect virtue allow the passive qualities and virtues traditionally attributed to women (shyness, chastity, modesty, humility, and the like) to be considered less valuable than ‘heroic’ masculine virtues. Aristotle’s idea that women are weaker in every respect due to their nature allowed the medical theory of bodily fluids to be used as proof of their imperfection, claiming that due to the warm and moist state of their bodies they are not inclined towards wisdom and patience. Women’s weak nature raised the question of whether they were capable of achieving virtue at all, whether they were moral beings, and whether they should have personal freedom or depend on their guardian, the man. The answers to these questions varied, ranging from the extremely conservative view that women, who are capable of practicing only imperfect virtues, must fully obey their father, husband, or other male guardian, to the somewhat more optimistic yet still conservative belief that women, as moral beings, must practice virtue in a feminine (i.e., traditionally passive) way, and men must not control them but rather take care of and provide for them.